(untitled) (Research, Society and Development, 2021)
Leprosy is a chronic infectious disease caused by the bacillus Mycobacterium leprae, with a highly transmissible and relevant character within the Brazilian public health scenario. Studies point out that in the northern region there was a significant increase in cases detected at an advanced stage of the disease, with a high degree of functional disability, which emphasizes the prevalence of a late diagnosis in this location, as well as factors that directly influence the recognition and treatment disease, such as socioeconomic aspects and lack of knowledge about the disease. Thus, this study aimed to promote the recognition of the main aspects involving leprosy, its mitigation and users’ autonomy through the main preventive measures of this pathology. The present study has a qualitative and descriptive approach, being an experience report about the interdisciplinary experience of health students during educational activities, based on the Arco de Maguerez, in a health unit in Belém-PA. As a result, many users of the unit were withdrawn at the beginning of the actions, however, there was greater enthusiasm after incentives. Furthermore, during conversations with the local population, it was clear that little knowledge of the disease was found, which corroborates its importance within health services. In addition, the target audience reiterated the importance of the activity for the prevention of severe cases of the disease and invited the academic team to return with other educational activities. The importance of leprosy prophylaxis in the primary care environment was identified, in addition to the role of the academic when acquiring skills for a future profession, based on a holistic view.